Neuravnotežena čezmejna javna sfera: nesorazmerna prisotnost Slovenije in slovenske manjšine v Italiji v javnomnenjskih procesih - Sekloča, Peter (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2008)
Unbalanced cross-border public sphere: disproportionate presence of Slovenia and Slovene minority in Italy in the public opinion formation processes. By the evaluation of the attention of minority press and Slovene national press to the events in Slovenia and among the Slovene minority in Italy respectively,and by the analysis of conflicts between Slovenia and minority, the author analyses the cross-border public communication processes. The method used for empirical analysis was the quantitative content analysis of minority and national newspapers. Public communication between the nation state of Slovenia and the minority was, by the comparison of contemporary theories of the public sphere, conceptualized as a public discussion about problems on broader spheres of politics, economy and civil society. The results of the analysis show that cross-border communication processes are marked by disproportionate participation and influence of public actors. This entails continuous endeavour of the minority to become recognized and respected partner in public discussion, whereas the Slovene actors have the power to overlook conflicts, which by minority's opinion are mainly produced by the Slovene political system. Media interfere in public discussion as distributors of subsided information, however, only the minority is interested in subsidization, whereas the actors from Slovenia are - because of their power - the inevitable object of attention of minority and its media at almost all problems that are of concern of both the minority and the actors from Slovenia.
Keywords: Italija; Italy; narodne manjšine; zamejski Slovenci; mass media; množični mediji; komuniciranje; communication; vpliv